Managing supply chain risk : integrating with risk management - Curkovic, Sime; Scannell, Thomas; Wagner, Bret (CRC Press, 2016)
Risk management in supply chain logistics has moved from being a nice-to-have to a necessity due to the number of variables that can cripple a business. Managing Supply Chain Risk: Integrating with Risk Management details the critical factors involved in managing supply chain risk. It discusses how managing supply chain risk can be integrated into Enterprise Risk Management (ERM) applications, focusing on the Committee of Sponsoring Organizations (COSO), Failure Mode Effects and Analysis (FMEA), and International Organization of Standards (ISO) 31000:2009 frameworks.- Resumé vydavatele
Keywords: logistika (management); rizikový management; business logistics; risk management; monografie; elektronické knihy; monographs; electronic books